PENDIDIKAN (AGAMA) ISLAM DI PERGURUAN TINGGI: TAWARAN DIMENSI ESOTERIK AGAMA UNTUK PENGUATAN SDM - Rusydi Sulaiman (Jurnal Madania)
IslamicEducation in University Level: An Offer of Religious Esoteric Dimension for Strengthening Human Resource. The term of PI (Pendidikan Islam) and PAI (Pendidikan Agama Islam) have been being discussed among lectures. Which one is more general than other? Conceptually, both terms are not too fixed. Hence, it should be clear the meaning then to be one paragdigm. In fact, some alumna of Tarbiyah Faculty who took this program are doubtful how to strengthen the concept of PAI (Pendidikan Agama Islam). This article is attempted to answer and make a concept of the paradigm of PAI (Pendidikan Agama Islam). According to its subject, PAI consists of three aspects; aqidah, sharia and akhlaq. It is different in certain aspects, such as: institution’s level, the qualification of student, subject’s period and teacher’s/lecture’s understanding. This study also offers an opinion—strengthening esoteric dimensio to students, lectures and officers in order to be an integrated persons. The formal esoteric dimension indicates esoteric weakness